TEKNIK PENGOLAHAN IKAN TERI (Stolephorus Sp.) DI PELABUHAN PERIKANAN PANTAI WILAYAH I CAROCOK ANAU TARUSAN KABUPATEN PESISIR SELATAN SUMATERA BARAT - Sri Maryeni; Windi Saputri (SEMAH Jurnal Pengelolaan Sumberdaya Perairan, 2022)
An area has its own uniqueness in the processing and handling of anchovy (Stolephorus Sp.) resources. The research objective was to find out about the procedures or techniques for making salted anchovies at the Coastal Fishing Port (PPP) Region 1 Carocok Anau, South Coastal District, West Sumatra Province. Observation research method and direct observation of the field were selected, the technique was by interviewing and filling out questionnaires where the selection of respondents was carried out by purposive sampling. Then the data were analyzed descriptively. The results showed that the processing techniques for salted anchovies at PPP Carocok Anau Tarusan were almost the same in general, starting from the method of receiving raw materials, washing, boiling, draining, salting, drying, and packaging/storage. Good anchovy processing techniques can produce quality and hygienic anchovy products